Incomes from the forest: methods for the development and conservation of forest products for local communities - Wollenberg, Eva Karoline; Ingles, A. (Center for International Forestry Research, 1998)
In the last two decades, there has been increasing interest in the potential of small-scale non-timber forest product collection and other low-impact uses of the forest for achieving forest conservation. Experience suggests however that such uses do not guarantee conservation and economic outcomes. This book documents and compares methods to assess options for forest-based livelihoods and their outcomes. The contributions are based on the premise that livelihood and conservation goals can be best achieved by improving information flows about changes in the environment, and the impacts of forest use. The 16 authors report on the strengths and weaknesses of methods that have been tried in the field. Their experiences and analysis should be of interest to practitioners everywhere concerned with developing livelihood options for people living in forests.